Sacred Texts and Their Subjects, Now and Then. Issue 1 (2nd November 2021) - George, Mark K.
Abstract : As the digital revolution extends to the ways people encounter sacred texts such as the Bible, a change is underway both with respect to the texts and to the readers of them. Technologies offer (i.e., afford) possibilities to their users, and these alter the ways in which those users understand and form themselves. Thus, print Bibles create different types of readers than do digital Bibles, even if the content of the Bible does not change. These changes are disruptive for some yet also offer new possibilities for the Bible and its readers. This article considers several affordances of print and digital Bibles before turning to a consideration of how those of digital Bibles are likely to change the subjectivity of readers.